Ações coletivas e sustentabilidade: uma análise da produção de frutas, verduras e legumes na microrregião de Toledo-PR - Santos, Leandro Pereira dos (2018)
The motivation for this research arose from the interest in studying the possible impact of participation in collective actions on the level of sustainability of agricultural producers. Specifically, the purpose was to estimate the impact of participation in cooperatives and associations. The literature that deals with the possible benefits derived from participation in collective actions has progressed. In this context, an empirical work that examines the impact of participation in collective actions on the sustainability of agricultural producers is important, considering the three dimensions of sustainability, that is, the economic, social and environmental dimensions. In particular, in terms of scope, the work was carried out in the agricultural productive sector of fruits and vegetables of the microregion of Toledo, PR, and the level of sustainability of the producers was measured through 16 indicators of sustainability in agriculture, selected with based on the literature on the subject. In this sense, the objective of this work was to analyze the impact of participation in collective actions at the level of economic, social and environmental sustainability of the agricultural producers of fruits and vegetables of the microregion of Toledo, PR. Empirical data were obtained through the application of questionnaires and interviews with these agricultural producers. For the analysis of the data collected, the cross-sectional data analysis with the IPWRA (Inversity Probability Weight Regression Adjustment) method was used to estimate the average treatment effect, in this case, the participation in cooperatives or producer associations. The analysis was complemented, in a qualitative perspective, with the answers to the open questions that compose the applied questionnaire, as well as the direct observation of the researcher in the visits made. The results of the research indicated that in the productive sector of fruits and vegetables in the microregion of Toledo-PR, participation in collective actions has a positive impact on the level of sustainability of farmers. However, the effect was verified in a differentiated way between the dimensions, being stronger in the economic dimension and weaker in the social and environmental dimensions. These results contribute to the consolidation of the literature that has demonstrated the economic benefits of participating in collective actions and also allows the cooperatives and associations of agricultural producers of fruits and vegetables of the microregion of Toledo, PR to incorporate into their guidelines new matter that can bring improvements in the levels of social and environmental sustainability for the sector.